(3GdeONd Edi Ydhe GdEYdGe h GdGJUGd (B:s (3OQGSI aj GdeaGgje h GdhSGFd h GdJfXjQ (B/s - (3HgfGS, SYjO YGOds ((3GdLRGFQ (B:s (3LShQ ddfTQ h GdJhRjY ,s, 2022)
(3GdGYdGe h GdGJUGd h GdaQhb HjfgeG GfhGY GdGJUGd GdeaGgje GdeTGHgI ddGYdGe h GdGJUGd s
(3HHdjhZQGajG (B: (3U(B.136-145s
Keywords: (3GdEYdGe h GdGJUGds